Prevalence of Periodontal Diseases Among Individuals Above 45 Years: A Retrospective Study - B, GEETHIKA.; RAJASEKAR, ARVINA; CHAUDARY, MANJARI (The journal of contemporary issues in business and government, 2021)
Periodontal disease ranges from gingival inflammation to loss of teeth and supporting structures. The aim of this study was to assess the periodontal health among individuals above the age of 45 years. This retrospective study was conducted using the case sheets of the patients in a private institution between June 2019 to March 2020. A total of 242 patients were randomly recruited. Data regarding the patient’s periodontal status were collected from the case records and analysed. Descriptive statistics and inferential statistics were done using SPSS software, Version Among the 242 patients, 29 patients (11.96%) exhibited generalised chronic gingivitis, 32 patients (13.22%) exhibited clinically healthy gingiva and 181 patients (74.79%) exhibited generalised chronic periodontitis. Clinically healthy gingiva was highly prevalent(37.5%) among 45-54 year old patients. Generalised chronic periodontitis(27.1%) and generalised chronic gingivitis(31.0%) was highly prevalent among 65-74 year old patients. The association between age and periodontal status was statistically significant(p=0.016) Clinically healthy gingiva(75%), generalised chronic gingivitis(79.3%) and generalised chronic periodontitis(89.3%) were more prevalent among the males. The association between gender and the periodontal health was statistically not significant(p value=0.604).